Mathematical modelling and analysis of dynamic behaviour for seeded batch potash alum crystallization process - Siti Zubaidah, Adnan; Noor Asma Fazli, Abdul Samad (AIP Publishing, 2022)
Solubility phase diagram which consists of information on solute concentration, metastable and saturation limits against temperature, provides helpful insights in designing crystallization process to achieve desired crystal size distribution (CSD). Usually, the design of cooling crystallization process involves high supersaturation level at the beginning of the process in the metastable zone that is bounded by metastable and saturation limits. However, this high level of supersaturation causes an increment in both nucleation and crystal growth rates which induce the growth of the seed crystals as well as unwanted secondary nucleation that produce excessive fine crystals. Mitigation by employing proper temperature trajectory or policy along metastable zone to avoid unnecessary long operational time and fine crystals is needed. Thus, the purpose of this paper is to develop and simulate mathematical model of seeded batch crystallization process for the case of potash alum which is mainly used for purification in water treatment. Dynamic response of such process under open-loop operation for three cooling policies which are natural, linear and cubic is performed for evaluating the effect of different cooling policies on CSD. Simulation results based on the dynamic behaviour for all three cooling policies show cubic cooling policy obtained the best performance by achieving mean crystal size of 420 µm from the targeted CSD at 430 µm, and the mean crystal size for fine crystals is the lowest which is 35 µm compared to linear and natural cooling policies, at 40 µm and 55 µm, respectively. This information is prominent in deciding proper temperature trajectory of optimal cooling policy for potash alum crystallization process.